Can a Real Business Cycle Model without price and wage stickiness explain UK real exchange rate behaviour? - David Meenagh; Patrick Minford; Eric Nowell; Prakriti Sofat (Cardiff University, Cardiff Business School, 2005)
This paper establishes the ability of a Real Business Cycle model to account for real exchange rate behaviour, using UK data. We show that a productivity simulation is capable of explaining initial real appreciation with subsequent depreciation to a lower steady state. The model is tested by the method of indirect inference, bootstrapping the errors to generate 95% confidence limits for a time-series representation of the real exchange rate, as well as for various key data moments. The results suggest RBC models can explain real exchange rate movements.
Keywords: E32; F31; F41; 330; Real Exchange Rate; Productivity; Real Business Cycle; Bootstrap; Indirect Inference